EPLAR — The echocardiographic Pulmonary to Left Atrial Ratio — A novel non-invasive parameter to differentiate pre-capillary and post-capillary pulmonary hypertension. (1st June 2016) - Scalia, Gregory M.; Scalia, Isabel G.; Kierle, Rebecca; Beaumont, Rebekka; Cross, David B.; Feenstra, John; Burstow, Darryl J.; Fitzgerald, Benjamin T.; Platts, David G.
Abstract: Background: Right heart catheterisation is the gold-standard for differentiating pre-capillary pulmonary hypertension (high mean pulmonary artery pressure, normal pulmonary wedge pressure) from post-capillary physiology (elevated pulmonary wedge pressure). The new non-invasive parameter, ePLAR (echocardiographic Pulmonary to Left Atrial Ratio) is calculated from the maximum tricuspid regurgitation continuous wave Doppler velocity (m/s) divided by the transmitral E-wave:septal mitral annular Doppler Tissue Imaging e′-wave ratio (TRVmax /E:e′). Methods: Pulmonary hypertension patients (mean pulmonary artery pressure > 25 mm Hg, n = 133, 66 male, average 65.0 ± 16.8 years) were classified by right heart catheterisation as pre-capillary or post-capillary [subdivided into isolated post-capillary (diastolic pulmonary gradient < 7 mm Hg) or combined pre- and post-capillary cases]. The ePLAR values of these groups were compared to each other and to a population sample of 16, 356 population reference echocardiograms. Results: ePLAR values for the normal reference population of 16, 356 echocardiograms (age 56 ± 16.6 years) were 0.30 ± 0.09 m/s. Pre-capillary pulmonary hypertension patients (n = 35, 26 male, PAPsys 63.9 ± 16.6 mm Hg, PAPdiast 24.1 ± 7.3 mm Hg, PAPmean 37.9 ± 9.4 mm Hg, PCWP 10.6 ± 2.7 mm Hg) had significantly higher ePLAR values than post-capillary cases (n = 98, 40 male, PAPsys 59.9 ± 17.6 mm Hg, PAPdiast 25.0 ± 7.4 mm Hg, PAPmean 38.1 ± 9.8 mm Hg, PCWP 23.5 ± 6.4 mm Hg) − ePLAR 0.44 ± 0.22 m/s vs 0.20 ± 0.11 m/s (p < 0.001). ePLAR values were significantly lower in isolated post-capillary pulmonary hypertension than in combined pre- and post-capillary cases (0.18 ± 0.08 m/s vs 0.28 ± 0.18 m/s, p < 0.001). Conclusions: ePLAR is a simple echocardiographic parameter which can accurately differentiate the smaller subset of patients with pre-capillary pulmonary hypertension from the more common post-capillary aetiology. The use of this easily obtained echocardiographic parameter has the potential to enhance non-invasive triage of patients for specific pulmonary vasodilator therapy.